The genetic structure and diversity of smallholder dairy cattle in Rwanda - Oluyinka Opoola; Felicien Shumbusho; Innocent Rwamuhizi; Isidore Houaga; David Harvey; David Hambrook; Kellie Watson; Mizeck G. G. Chagunda; Raphael Mrode; Appolinaire Djikeng (BMC Genomic Data)
Abstract Previous genomic characterisation of Rwanda dairy cattle predominantly focused on the One Cow per Poor Family (locally called “Girinka”) programme. However, smallholder farmers in Rwanda have benefited from other livestock initiatives and development programmes. Capturing and documenting the genetic diversity, is critical in part as a key contribution to genomic resource required to support dairy development in Rwanda. A total of 2,229 crossbred animals located in all dairy-producing regions of Rwanda were sampled. For each animal, a hair sample was collected and genotyped by using the Geneseek Genomic Profiler (GGP, Neogen Geneseek®) Bovine 50 K (n = 1,917) and GGP Bovine 100 K arrays (n = 312). The combined dataset was subject to quality control, data curation for use in population genetics and genomic analyses. To assess the genetic structure and diversity of the current population, key analyses for population structure were applied: Principal Component Analysis (PCA), population structure and diversity, admixture analysis, measures of heterozygosity, runs of homozygosity (ROH) and minor allelic frequency (MAF). A dataset of global dairy population of European taurine, African indicus and African taurus (n = 250) was used as reference. Results showed that Rwanda cattle population is highly admixed of diverse pure and crossbred animals with average MAF of 33% (standard error; se = 0.001) with proportion of foreign high yielding (taurine) dairy breeds of Jersey Island (18%); 12% non-Island Jersey and 42% Holstein-Friesian ancestries. Two African Bos taurus and five Bos indicus breeds contributed 28% of their genetics. Genetic distances were highest in Gir and N’dama (0.29); and Nelore and N’dama (0.29). There were 1,331 ROH regions and average heterozygosity were high for Rwanda cattle (0.41 se = 0.001). Asides well-established genes in cattle, we found evidence for a variety of novel and less-known genes under selection to be associated with fertility, milk production, innate immunity and environmental adaptation. This observed diversity offers opportunity to decipher the presence and/or lack of genetic variations to initiate short- and long-term breed improvement programmes for adaptation traits, disease resistance, heat tolerance, productivity and profitability of smallholder dairy systems in Rwanda.